Neural Representations of Concreteness and Concrete Concepts Are Specific to the Individual - Botch, Thomas L.; Finn, Emily S. (The Journal of neuroscience, 2024)
Different people listening to the same story may converge upon a largely shared interpretation while still developing idiosyncratic experiences atop that shared foundation. What linguistic properties support this individualized experience of natural language? Here, we investigate how the “concrete–abstract” axis—the extent to which a word is grounded in sensory experience—relates to within- and across-subject variability in the neural representations of language. Leveraging a dataset of human participants of both sexes who each listened to four auditory stories while undergoing functional magnetic resonance imaging, we demonstrate that neural representations of “concreteness” are both reliable across stories and relatively unique to individuals, while neural representations of “abstractness” are variable both within individuals and across the population. Using natural language processing tools, we show that concrete words exhibit similar neural representations despite spanning larger distances within a high-dimensional semantic space, which potentially reflects an underlying representational signature of sensory experience—namely, imageability—shared by concrete words but absent from abstract words. Our findings situate the concrete–abstract axis as a core dimension that supports both shared and individualized representations of natural language.